Comprehensive Map of the Artemisia annua Proteome and Quantification of Differential Protein Expression in Chemotypes Producing High versus Low Content of Artemisinin. Issue 10 (18th May 2020) - Chen, Minghui; Yan, Tingxiang; Ji, Liyun; Dong, Yu; Sidoli, Simone; Yuan, Zuofei; Cai, Chunlin; Chen, Jiwei; Tang, Yueli; Shen, Qian; Pan, Qifang; Fu, Xueqing; et al.
Abstract: Artemisia annua is well known for biosynthesizing the antimalarial drug artemisinin. Here, a global proteomic profiling of A. annua is conducted with identification of a total of 13 403 proteins based on the genome sequence annotation database. Furthermore, a spectral library is generated to perform quantitative proteomic analysis using data independent acquisition mass spectrometry. Specifically, proteins between two chemotypes that produce high (HAP) and low (LAP) artemisinin content, respectively, are comprehensively quantified and compared. 182 proteins are identified with abundance significantly different between these two chemotypes means after the statistic use the p‐value and fold change it is found 182 proteins can reach the demand conditions which represent the expression are significantly different between the high artemisnin content plants (HAPs) and the low artemisnin content plants (LAPs). Data are available via ProteomeXchange with identifier PXD015547. Overall, this current study globally identifies the proteome of A. annua and quantitatively compares the targeted sub‐proteomes between the two cultivars of HAP and LAP, providing systematic information on metabolic pathways of A. annua .